CEDRIC PRICE AND GORDON PASK: THE JAPAN NET EXPERIMENT (1986)
This paper focus architect Cedric Price and cybernetician Gordon Pask collaboration around the almost unknown Japan Net project (1986). I state that Price's architectural premises had a unique expression in this project due to Pask's effort. The proposal envisioned the city as an ample evolving system, expressing Pask's own second- order ideas and advancing a unique contribution to to- day's I.S. debate on an evolving hybrid environment. (REF: FURTADO, Gonçalo, "Cedric Price and Gordon Pask: The Japan Net Experiment (1986)", in: TRAPLL, Robert (ed.), Vienna: Austrian Society for Cybernetic Studies, EMCSR 2008, pp.138-143.)